On the Generative Utility of Cyclic Conditionals - Liu, Chang; Tang, Haoyue; Qin, Tao; Wang, Jintao; Liu, Tie-Yan (NeurIPS 2021, 2021)
We study whether and how can we model a joint distribution p(x,z) using two conditional models p(x|z) and q(z|x) that form a cycle. This is motivated by the observation that deep generative models, in addition to a likelihood model p(x|z), often also use an inference model q(z|x) for data representation, but they rely on a usually uninformative prior distribution p(z) to define a joint distribution, which may render problems like posterior collapse and manifold mismatch. To explore the possibility to model a joint distribution using only p(x|z) and q(z|x), we study their compatibility and determinacy, corresponding to the existence and uniqueness of a joint distribution whose conditional distributions coincide with them. We develop a general theory for novel and operable equivalence criteria for compatibility, and sufficient conditions for determinacy. Based on the theory, we propose the CyGen framework for cyclic-conditional generative modeling, including methods to enforce compatibility and use the determined distribution to fit and generate data. With the prior constraint removed, CyGen better fits data and captures more representative features, supported by experiments showing better generation and downstream classification performance.